Computational logistics : 9th International Conference, ICCL 2018, Vietri sul Mare, Italy, October 1-3, 2018, Proceedings /: 9th International Conference, ICCL 2018, Vietri sul Mare, Italy, October 1-3, 2018, Proceedings. (2018) - Unknown
No abstract available